Metal detector movable vehicle / Muhammad Zahid Tajuddin & Zamsuri Mohd Fadhli - Tajuddin, Muhammad Zahid; Mohd Fadhli, Zamsuri (2015)
The intention of this project is to design a device, which is capable of detecting hidden metal whose location is controlled by a remote Android application. The proposed system uses a arduino uno and a battery for power source. This project consists of a metal detector circuit for sensing any metallic object present in land mines. A Bluetooth transceiver is interfaced to the microcontroller for communication. Two motors are connected to the microcontroller with the help of a motor driver IC wherein they are used to control the device. Once the communication is established from the user phone to this system through a Bluetooth then the user can send the control signals to this system. When the user enters commands on the Android application with GUI, the corresponding robot's direction is changed. A metal detector circuit is device such that whenever the robot while moving on the surface encounters any metallic object, it produces a beep sound as an indication of detected mines. The project in future can be enhanced by mounting a wireless camera on the robot so that the operator can control the movement of device